Efficient power allocation for cognitive radio NOMA using game-theoretic based pricing strategy - Abidrabbu, Shaima’ S.; Arslan, Hüseyin (Institute of Electrical and Electronics Engineers Inc., 2021)
Cognitive radio-based non-orthogonal multiple access (CR-NOMA) is considered to be one of the promising multiple accessing technique candidates for 5G and beyond networks. These networks are facing a lot of challenges to achieve high spectral efficiency, low latency, and massive connectivity. Interference management and efficient power allocation are highly interesting among the researchers to investigate in CR-NOMA networks. This paper studies the power allocation of underlay CR-NOMA network using game theory approach by conducting the pricing technique to achieve efficient power allocation and minimum interference. In particular, the game is formulated, and its solution is achieved by exploring the suboptimal solution represented by the Pareto-efficiency of the Nash equilibrium point. The simulation results show the superiority of the proposed scheme in achieving higher spectral efficiency, fairness index, and sum utilities of secondary users compared to existing schemes.
Keywords: Capacity; CR-NOMA; Game Theory; Power Allocation; Pricing; Spectrum Utilization